Farmers’ willingness to adopt sustainable agricultural practices: A meta-analysis - Boufous, Sawssan; Hudson, Darren; Carpio, Carlos (PLOS Sustainability and Transformation, 2023)
Author summary The increasing growth of consumption needs puts pressure on the natural system, harming climate, biodiversity, water, and environment which has induced a recognition that action should be taken to mitigate irreversible damage to the environment. Sustainability is believed to be obtainable through a change in consumer’s and producer’s behavior, which can be primarily done through the transformation of our agricultural system using alternative farming approaches that are based on ecological principles [1]. The literature is very expansive on analyzing farmers’ willingness to adopt sustainability but it is limited in providing WTA values. Thus, in our meta-analysis we focus on quantitative WTA studies to investigate the presence of a proxy for a true mean WTA for sustainable agriculture and detect the methodological variables that might affect the WTA value. We found a proxy for the mean WTA for sustainable farming ranging between 567 USD/ha/year and 709 USD/ha/year, as well as a proxy for WTA producing biomass crops ranging from 2054 USD/ha/year to 2766 USD/ha/year. Also, among the significant methodological variables that affect WTA values are the use of a non-random sampling method, and contingent valuation. The two methods are found to lead to higher WTA values than when random and conjoint valuation methods are used.